Dorm attendance / Muhammad Irfan Farhat Mohd Azali, Muhammad Aiman Rosman and Norsyahira Syafeq - Mohd Azali, Muhammad Irfan Farhat; Rosman, Muhammad Aiman; Syafeq, Norsyahira (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Datuk Seri Mohd Zin Vocational College has male and female dormitories, which can accommodate about 260 students. A separate block, within the college grounds. In the dormitory rules, students must be in the room at the appointed time. The purpose is to ensure that students are in the college grounds safely. The problem statement for our project is, the attendance of students in their respective rooms at the allotted time, is not reaching 100%. The head of the dorm will make a call several times to ensure that students enter the room, to be taken attendance by noting on the attendance book. This attendance management period takes more than 30 minutes. Once all the students are enough, the attendance should be sent to the warden on duty. The attendance book needs to be checked by the warden on duty. This routine happens every day. This will disrupt the sleep time of students and wardens. In the event of a no -entry case, the dorm head will search the college grounds. Our Dorm Attendance project is a tool for recording student attendance and the time they enter the room. This will make it easier for wardens to monitor the attendance of hostel students using smartphones. In the smartphone there is a cloud platform app. Things board that records the time and name of the student. Dorm Attendance is placed in each room and uses a fingerprint sensor to detect fingerprints. The student's name will be displayed on the LCD display. The objective of this study is to design the ESP8266 module Wi-Fi circuit to send information to the Things board cloud platform (lo T application.) Develop a program for the Dorm Attendance system, test the functionality of the ESP8266 circuit and fingerprint to facilitate wardens to take hostel students. The project has been tested and works well. The Arduino ATMEGA 328P kit is a chip that has been used as an electronic device control. The Proteus software program was developed to draw circuits and test the function of control circuits. The result of this product can help the warden to know the time and attendance of students in each room quickly. This product has limitations or scope of work. This product uses a supply voltage of 12v. It has an LCD display and a fingerprint sensor on the front of the model. Buzzer is used as an indicator component after the fingerprint is detected. It stores data on the Things board cloud platform. The warden will receive student attendance and time data. This product has worked well by reducing the duration of the effect of student attendance from 30 minutes to only 3 minutes. It is hoped that this product will facilitate the warden to act if student attendance is insufficient.